Physiological cold tolerance evolves faster than climatic niches in plants - Wen, Yin; Ye, Qing; Román-Palacios, Cristian; Liu, Hui; Wu, Guilin (Frontiers in Plant Science, 2023)
Understanding how plants respond to thermal stress is central for predicting plant responses and community dynamics in natural ecosystems under projected scenarios of climate change. Although physiological tolerance is suggested to evolve slower than climatic niches, this comparison remains to be addressed in plants from a phylogenetic comparative approach. In this study, we compared (i) the evolutionary rates of physiological tolerance to extreme temperatures with (ii) the corresponding rates of climatic niche across three major vascular plant groups. We further accounted for the potential effects of hardening when examining the association between physiological and climatic niche rates. We found that physiological cold tolerance evolves faster than heat tolerance in all three groups. Coldest climatic-niche temperatures evolve faster than warmest climatic-niche temperatures. Importantly, evolutionary rates of physiological cold tolerance were faster than rates of change in climatic niche. However, an inverse association between physiological cold tolerance and responding climatic niche for species without hardening was detected. Our results indicated that plants may be sensitive to changes in warmer temperatures due to the relatively slower evolutionary rates of heat tolerance. This pattern has deep implication on the framework that is being used to estimate climate-related extinctions over the upcoming century.